Analisis Literatur Review: Penggunaan Teknik Modelling Menggunakan Pendekatan Cognitive Behavioral Therapy Untuk Konsentrasi Siswa Dalam Belajar - Rachman Hakim; Firman Firman; Netrawati Netrawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Student learning concentration is a very important thing to pay attention to in the learning process to achieve effective and efficient learning so as to get good learning results. To increase the concentration of post-pandemic students, of course, they find things that are different from the ideal, namely in the phenomenon that students often pay less attention to the teacher when explaining during the learning process, disturb friends and often ask when to go home before the school's set time to go home. This must be overcome so that the concentration of student learning increases and returns to normal conditions in participating in learning. Modeling techniques with the CBT approach are used to increase student learning concentration which is low after the covi-19 pandemic. Learning takes place through a process of imitation, not only by imitation but by adding or eliminating behavior, such as not concentrating while studying.